MiR-21 as prognostic biomarker in head and neck squamous cell carcinoma patients undergoing an organ preservation protocol - Arantes, Lidia Maria Rebolho Batista (Oncotarget, 2016)
Despite progress in the treatment of head and neck squamous cell carcinoma (HNSCC) in recent decades, including new surgical techniques, radiotherapy advances and chemotherapy schedules, the prognosis for the affected patients has not improved at the same pace, and still, most HNSCC patients are diagnosed in advanced stages. To increase their survival, the development of better screening methods for early detection is required and appropriate tailored therapeutic interventions are desired. The aim of the present study was to evaluate miRNAs as prognostic biomarkers in patients undergoing organ preservation protocol for locally advanced HNSCC. For this purpose, we assessed the global miRNA expression profile of 15 HNSCC patients (‘screening set’) to identify miRNAs differentially expressed in responders and non-responders to therapy. Four miRNAs differentially expressed in HNSCC samples from the ‘screening set’ were validated in a different cohort of patients (47 samples - ‘validation set’). The results from the ‘validation set’ showed that the higher expression of one of these miRNAs, miR-21, was negatively associated with the treatment response to the organ preservation protocol (p=0.029). A multivariate analysis showed that, in a model adjusted for age, tumor site, p16 immunoexpression and tumor resectability, high expression of miR-21 remained an independent predictor of poor response to the organ preservation protocol (OR=5.69; 95%CI 1.27-25.58; p=0.023), together with clinical stage IV (OR=5.05; 95%CI 1.22-20.88; p=0.025). Furthermore, considering the entire cohort, patients with high expression of miR-21 had worse survival. A multivariate Cox regression analysis also showed miR-21 (HR=2.05; 95%CI 1.05-4.02; p=0.036) and clinical stage IV (HR=3.17; 95%CI 1.49-6.77; p=0.003) as independent prognostic factors (model adjusted for age, tumor site, tumor resectability, and sets ‘screening’ or ‘validation’). In conclusion, the results of this study suggest that the evaluation of miR-21 expression could be an important tool for treatment planning and a prognosis predictior for HNSCC patients undergoing organ preservation protocols.